ANALYSIS OF A01 RAW MATERIAL REQUIREMENT PLANNING USING THE LOT SIZING WAGNER WITHIN, LOT FOR LOT, AND PERIOD ORDER QUANTITY - Sugara, Yusuf; Mursalina, Tasya; Majid, Fairuz; Rismayanti, Zani; Taziri, Muchamad Iqbal Taufik; Fauzi, Muchammad (CENTRAL ASIA AND THE CAUCASUS, 2004)
PT. XYZ is engaged in manufacturing painting which produces various types of decorative paints. One of the products with the highest sales capacity is CK ABC 901; The main raw material in producing this CK ABC 901 is A01 with a total usage of 35.85%. The main raw material greatly affects most of the production process. The problem faced by the company is the absence of resources which control the inventory of raw materials every month. Thus it causes the purchase of raw materials not in accordance with consumer demand and causes problems at the costs that should be minimized. Therefore, the company needs to control the supply of the raw materials so that the production process. One of the methods used in overcomingcompany problems is Material Requirements Planning with data processing obtained from ARIMA forecasting results using the Crystal Ball application. Forecasting results are used as input in determining the amount of raw material or lot size which needs to be provided to carry out the production process. This research focuses on lot sizing method of LFL, POQ and Wagner Within to get the minimum total cost of inventory. The results of calculations using the MRP method obtained that the total cost of raw material inventory using the technique of the lotting algorithm of Wagner Within is Rp. 1,967,376. Where the fulfillment of raw materials is carried out 6 times, namely December 2020, February, March, April, June, August and October 2021 with a total order of 4399 Kg, 3697 Kg, 3358 Kg, 3173 Kg, 3836 Kg, and 4242 Kg.